Electrochemically induced Meerwein arylation as a green strategy for the synthesis of arylbenzoquinone derivatives under batch and flow conditions - Mozhdeh Malmir; Davood Nematollahi; Ali Sadatnabi; Sajad Shanehsaz (Scientific Reports)
Abstract An electrochemical Meerwein arylation reaction was reported for the synthesis of aryl-benzoquinone derivatives. In this work, efficient electrochemical synthesis of aryl-benzoquinone derivatives by direct electrolysis of aqueous solution containing hydroquinone and aryldiazonium salts in batch and a homemade continuous-flow cells is reported. In the batch system, the products were obtained in a simple undivided cell equipped with a copper anode and a stainless steel cathode. In the continuous flow system, the products were obtained simply by passing hydroquinone and the aryldiazonium salt through a tube made of copper with a stainless steel rod in the center. All equipment required in both cell types is obtained from common commercial sources. This protocol is green and cost-effective due to the use of electricity and is performed under mild and safe conditions without the use of toxic solvents and catalysts.